Correlation between Endosonographic and Doppler Ultrasound Features of Portal Hypertension in Patients with Cirrhosis. (31st October 2011) - Wiechowska-Kozłowska, A.; Zasada, K.; Milkiewicz, M.; Milkiewicz, P.
Abstract : Purpose . Endoscopic ultrasound (EUS) permits the detailed visualization of clinically significant features of portal hypertension; however, it is an invasive procedure that is not widely available. The aim of this cross-sectional study was to determine whether a correlation exists between the features of portal hypertension detected using both Doppler ultrasound and EUS in subjects with liver cirrhosis. Materials and Methods . Analyzed cohort included 42 patients who underwent a detailed Doppler ultrasound focusing on the parameters of blood flow in the portal/splenic vein as well as an endoscopic/EUS procedure that included the assessment of the size and localization of "deep" varices. Results . The size of "deep" oesophageal varices detected with EUS exhibited no correlation with the parameters assessed by Doppler ultrasound. However, the size of the "deep" gastric varices detected using EUS correlated with the time averaged maximum velocity (T max as well as V min, V max ) for the portal vein using Doppler ultrasound and exhibited a correlation with the V max and T max for the splenic vein. No significant correlation was determined between the diameter of the azygous vein and the thickness of the gastric wall when seen on EUS versus the parameters measured with Doppler ultrasound. Conclusion . EUS provides important information regarding the features of portal hypertension, and in the case of "deep" oesophageal varices exhibits a limited correlation with the parameters detected by Doppler ultrasound. Thus, despite its invasiveness, EUS is a method that provides a reliable and unique assessment of the features of portal hypertension in patients with liver cirrhosis.